Comparison Between Taichi Chuan and Jacobsonâs Progressive Muscular Relaxation in Decreasing Cortisol Concentration on Pre-Hypertension Patients - Kesoema, Tanti Ajoe; Chasani, Shofa; Chasani, Shofa; Handoyo, Rudy; Handoyo, Rudy (Jurnal Kesehatan Masyarakat, 2016)
Nowadays, the prevalence of hypertension and its concomitant risk of cardiovascular and kidney disease development is increasing as the disability evidence in the society also rises. One of the potential risk factors of prehypertension is anxiety and it has already well-known that cortisol is a marker of anxiety. There are some nonpharmacologic methods to relieve anxiety: exercise and relaxation. Taichi Chuan is a low intensity aerobic exercise that also gives a relaxation effect.This study is organised to find out the effect of Taichi Chuan (TCC) and Jacobsonâs Progressive Muscular Relaxation (JPMR) on cortisol level in pre hypertension patients. This is a pre and post-test design study with a total of 26 pre hypertension patients included. They were randomly divided into 2 groups. Group I performed Taichi Chuan exercise, while group II performed JPMR for 18 times. The intervention frequency was 3x/week for 6 weeks with 30 minutes duration for each session. In the study, which was held in April-June 2015, there was a decrease but no significant difference of cortisol concentration in both group.The comparison between groups also did not show statistical difference. However there were significant difference noted on the blood pressure before and after intervention in both groups.